2007
DOI: 10.1063/1.2801404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the density of collision cascades on ion implantation damage in ZnO

Abstract: We study structural disorder in ZnO bombarded at room temperature with 1.3 keV∕amu atomic P and cluster PFn (n=2 and 4) ions. Rutherford backscattering/channeling spectrometry results show that the density of collision cascades has a negligible effect on the damage buildup in the crystal bulk in the dose range resulting in ∼1.5−15 displacements per atom. Hence, the amount of stable post-implantation disorder in the bulk can be predicted based on ballistic calculations. In contrast, the cascade density affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Previous experiments for different materials have revealed that the efficiency of the formation of stable damage generally increases with increasing m 6891013161718193132. However, even the qualitative behavior is non-trivial and depends strongly on the material and irradiation conditions such as Φ, F , and T .…”
Section: Resultsmentioning
confidence: 98%
“…Previous experiments for different materials have revealed that the efficiency of the formation of stable damage generally increases with increasing m 6891013161718193132. However, even the qualitative behavior is non-trivial and depends strongly on the material and irradiation conditions such as Φ, F , and T .…”
Section: Resultsmentioning
confidence: 98%
“…Perillat‐Merceroz et al observed two types of dislocation loops in N‐bombarded ZnO: one type oriented along basal planes and localized approximately within N ions range (basal loops) and a second one oriented along prismatic planes, localized in deeper regions (prismatic loops) . Azarov et al showed that damage buildup in ZnO does not depend on the density of collision cascades induced by bombarding ions. Based on these conclusions and supported by RBS/C and XRD measurements of 300 keV Ar‐bombarded ZnO, Turos et al proposed a model of formation of both basal and prismatic loops, which is independent of the bombarding ion mass and mediated by lattice stress.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO is transparent to visible light, cheap in production, and significantly resistant to ion bombardment. It has been observed not to be driven amorphous by different ion beams up to 100 displacements per atom (DPA) …”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, the "bulk" disorder saturates with increasing ion dose, and the damage accumulation exhibits an anomalous multipeak distribution when high-density collision cascades are generated. 12,13 In addition, annealing of the damage is often complicated by a surface degradation, caused by oxygen loss and change in material composition at high temperature ( 1000 • C). 14,15 In fact, changes in the surface morphology have been observed already after low-temperature anneals (>200 • C in nitrogen ambient environment and >300 • C in air), featured with an increased surface roughness.…”
Section: Introductionmentioning
confidence: 99%